Maqāșid Al-Qur’ān: Genealogi dan Peta Perkembangannya dalam Khazanah Keislaman - Ulya Fikriyati ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2019)
This article attempts to map the phases of maqasid al-Qur'an in Islamic sources. Searching for traces of developments and typologies of maqasid al-Qur'an is important to show its scientific genealogical side. To achieve the purpose, this article builds on two main questions: a) What is the definition of maqasid al-Qur'an?; b) How do the map of development of maqasid al-Qur'an in Islamic sources? Both of these questions lead to the conclusions: a) There is no agreement among the Islamic scholars on the definition of maqasid al-Qur'an. However, the definitions that exist refer to the core of Qur’anic teachings and objectives that must be developed according to the time and space where the Qur'an is read and understood; b) The development of maqasid al-Qur'an can be mapped into four categories: nucleus diaspora phase, pre-theoretical applicative phase, conceptual formative phase, and contextual transformative phase.